Debt Renegotiation: A Simple Model and Discussion for Understanding the Phenomenon (GESTIÓN Y TENDENCIAS, 2025)
This article analyzes the accelerated growth of personal debt renegotiation applications in Chile following the COVID-19 pandemic. While debt levels have historically been high in the country, the post-pandemic context presents unique dynamics. The authors propose a theoretical model to identify the economic and regulatory factors driving this trend, examining decision-making regarding renegotiation versus asset liquidation. The study posits that recent regulatory reforms have lowered barriers to entry for debtors, increasing the appeal of renegotiation. At the same time, the deterioration of the real estate market has reduced asset liquidity, giving creditors an incentive to prefer renegotiation in order to maximize loan recovery. The model shows that these combined forces have widened the range of asset values for which renegotiation proves to be the optimal outcome.
Keywords: personal debt; debt renegotiation; insolvency; real estate market